Adoption of Climate Resilient Agricultural Technologies by Farmers - Nanjappan, Balasubramani (Journal of Agricultural Extension Management, 2018)
Climate change affects the livelihood of farmers and hence there is a need forÂ  adaptation. The present study was conducted in two States from northern and southern parts of India viz., Uttarakhand and Karnataka respectively to find out the adaptation strategies followed by the respondents and various constraints involved in adopting climate resilient agriculture practices. The study reveals that a majority of the respondents (80.00%) have replaced long duration varieties with short duration varieties and adopted water conservation through Contour/ Graded bunds formation (75.56%).In addition they have also adopted improved agronomic practices such as crop rotation (88.88%), mulching (78.00%) and disease management of animals through regular vaccination (73.33%).A majority of the respondents (64.44%) have used custom hiring centers for undertaking timely operations. Meanwhile, they were facing various constraints in adopting climate resilient agricultural practices due to limited knowledge on climate resilient adaptation measures, inadequate number of extension functionaries at grass root level, and inadequate weather based farm advisories. Hence it is suggested that capacity building of farmers on several climate smart practices may be undertaken through various extension approaches for strengthening the farmers ability to tackle the ill effects of climate change.